“Dilahirkan, Bukan Dijadikan (‘γεννηθέντα οὐ ποιηθέντα’)”: Kelahiran Sang Putera dari Bapa Menurut Konsili Nikea - Febrianto, Paulus (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
The revelation of the Christian faith is not always apparent at first glance. This revelation is being contemplated constantly, especially when dealing with the challenges of the new era. One thing that cannot be spared from challenges is the understanding of faith in the divinity of Jesus Christ. One of the most significant periods occurred before the Council of Nicaea. The church had to face tough challenges that was coming from Arius. Therefore, how did the Fathers of the Council respond? This paper is aimed to review this theme.